Optimizing Green Vehicle Routing Problem for Halal and Non-Halal Products using Salp Swarm Algorithm - Marsetiya Utama, Dana; Leilani Salsabilah, Aisyah (Universitas Ahmad Dahlan, 2025)
Modern distribution systems must clearly distinguish between halal and non-halal items, particularly in areas with sizable Muslim populations and rising awareness of halal integrity. Consumer confidence may suffer, halal principles may be broken, and cross-contamination may result from failing to maintain this separation. This research uses the Green Vehicle Routing Problem (GVRP) approach, which is solved with the Salp Swarm Algorithm (SSA), to develop a joint distribution optimization model for halal and non-halal products in an effort to address these issues. With complete separation and adherence to halal logistics regulations, this methodology aims to reduce Total Distribution Cost (TDC), which comprises fuel expenses, carbon emissions, and operating costs. The SSA method is combined with Large Rank Value (LRV) to convert continuous solutions into practical and feasible route sequences. Simulation results using synthetic data from 20 customer locations show that increasing the population size and SSA iterations consistently reduces the TDC value until stable convergence is achieved. The model also proves to be robust to changes in fuel costs, emissions, and vehicles without altering the route structure. Overall, the results of the research show that the SSA-based GVRP model is capable of providing efficient and sustainable halal logistics solutions. The novelty of this research lies in the explicit integration of halal and non-halal segregation with the SSA-based GVRP optimization framework in a single sustainable distribution system.